SYSTEMATIC LITERATURE REVIEW: KANDUNGAN SENYAWA BIOAKTIF DAN AKTIVITAS SITOTOKSIK EKSTRAK ALANG-ALANG TERHADAP SEL KANKER - Nuh, Muhammad; Ma’rifah; Haq, Nasrul; Akrom (Jurnal Buana Farma, 2025)
Imperata cylindrica (Imperata cylindrica) is a traditional medicinal plant long used in various countries and is known to contain various bioactive compounds with anticancer potential. Research on the cytotoxic activity of Imperata cylindrica continues to develop, but results are still varied, requiring a systematic review to summarize the available scientific evidence. This study aims to review the bioactive compound content and cytotoxic activity of Imperata cylindrica extract against various cancer cells. A systematic literature review method was conducted by searching articles from international and national databases using relevant inclusion and exclusion criteria. Of the total 410 articles found, 10 articles were selected to meet the requirements for analysis. The results of the study showed that cogongrass extract with various solvents (ethanol, methanol, water, n-hexane fraction, ethyl acetate fraction, and chloroform) has cytotoxic activity against various cancer cell lines, such as breast (MCF-7), cervical (HeLa), colon (HT-29), lung (A549), liver (HepG2), prostate (PC-3), and leukemia (HL-60). The identified cytotoxic mechanisms include induction of apoptosis, cell cycle arrest, inhibition of migration, antioxidant, anti-inflammatory, and immunomodulatory activities. The dominant compounds that play a role include flavonoids, alkaloids, terpenoids, saponins, and tannins. In conclusion, cogongrass extract has great potential as a candidate for natural anticancer agents, although further research in the form of in vivo tests and clinical trials is still very necessary to ensure its effectiveness and safety.